Calcium influx, oxidative stress, and apoptosis induced by TRPV1 in chronic myeloid leukemia cells: Synergistic effects with imatinib - Maggi, Federica; Morelli, Maria Beatrice; Aguzzi, Cristina; Zeppa, Laura; Nabissi, Massimo; Polidori, Carlo; Santoni, Giorgio; Amantini, Consuelo (Frontiers in Molecular Biosciences, 2023)
Introduction: Calcium flux is the master second messenger that influences the proliferation–apoptosis balance. The ability of calcium flux alterations to reduce cell growth makes ion channels interesting targets for therapy. Among all, we focused on transient receptor potential vanilloid 1, a ligand-gated cation channel with selectivity for calcium. Its involvement in hematological malignancies is poorly investigated, especially in the field of chronic myeloid leukemia, a malignancy characterized by the accumulation of immature cells. Methods: FACS analysis, Western blot analysis, gene silencing, and cell viability assay were performed to investigate the activation of transient receptor potential vanilloid 1, by N-oleoyl-dopamine, in chronic myeloid leukemia cell lines. Results: We demonstrated that the triggering of transient receptor potential vanilloid 1 inhibits cell growth and promotes apoptosis of chronic myeloid leukemia cells. Its activation induced calcium influx, oxidative stress, ER stress, mitochondria dysfunction, and caspase activation. Interestingly, a synergistic effect exerted by N-oleoyl-dopamine and the standard drug imatinib was found. Conclusion: Overall, our results support that transient receptor potential vanilloid 1 activation could be a promising strategy to enhance conventional therapy and improve the management of chronic myeloid leukemia.